2019
DOI: 10.1038/s41598-019-53400-1
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed fire maintains host plants of a rare grassland butterfly

Abstract: As grassland ecosystems transform globally due to anthropogenic pressures, improvements in our understanding of the effect of management on rare and threatened species in such landscapes has become urgent. Although prescribed fire is a very efficient tool for habitat restoration and endangered species management on fire-adapted ecosystems, the specific mechanisms underlying potential effects of burning on population dynamics of butterfly host plants are poorly understood. We analyzed a 12-year dataset (2004–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
3
0
1
Order By: Relevance
“…In a separate study of the same landscape, we found the same site to differ from the others in both the prevalence and the abundance of wild violet plants ( Viola spp. ; Adamidis et al 2019), probably due to site‐level differences in topography, edaphic, or microclimatic conditions and disturbance history.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study of the same landscape, we found the same site to differ from the others in both the prevalence and the abundance of wild violet plants ( Viola spp. ; Adamidis et al 2019), probably due to site‐level differences in topography, edaphic, or microclimatic conditions and disturbance history.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we found that low fire frequency benefits the species that prefer shaded areas in mixed woodland and forest, like the Zulu shadefly (Online Appendix 1 Figure S3). Conversely, medium and high fire frequencies had positive effects on some open savanna species, such as the broadbordered grass yellow and the cupreous blue (Online Appendix 1 Figure S3), which are resilient to fire and promoted by frequent burning (Adamidis et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Se colocaron 8 transectos en total, cada uno con una longitud de 200 m, en ambas áreas de estudio, específicamente, 4 en el área afectada por el fuego y otros 4 en el área control. En los extremos de cada transecto, se delimitaron cuadrantes de 2 × 2 m (Adamidis et al, 2019;Gaigher et al, 2021;Serrat et al, 2015). En total, se designaron 16 cuadrantes de 4 m 2 , distribuidos equitativamente entre el sitio quemado y el sitio control, con el propósito de realizar observaciones y registros florales a lo largo de 1 año, abarcando los meses de febrero, marzo, mayo, junio, julio, agosto, noviembre de 2018 y enero de 2019. https://doi.org/10.…”
Section: Materiales Y Métodosunclassified